Effectiveness, efficiency, duration, and costs of recruiting for an African American women's lifestyle physical activity program. Issue 5 (14th June 2013) - Wilbur, JoEllen; Buchholz, Susan W.; Ingram, Diana M.; Braun, Lynne T.; Johnson, Tricia J.; Fogg, Louis; Miller, Arlene M.; Volgman, Annabelle S.; McDevitt, Judith
Abstract In a 48‐week lifestyle physical activity controlled trial in African American women, we analyzed recruitment effectiveness, efficiency, duration, and costs. Social networking was the most effective approach for inviting women to the trial. Of the 609 who responded to invitations, 514 completed telephone screening; of these, 409 (80%) were found eligible. The health assessment screening was completed by 337 women; of these, 297 (88%) were found eligible. The mean number of days from completion of the telephone and health assessment screenings to beginning the intervention was 23.01, and the mean cost was $74.57 per person. Results suggest that provision of health assessment screening by study staff as part of recruitment is effective for minimizing attrition and also might be cost‐effective. © 2013 Wiley Periodicals, Inc. Res Nurs Health 36: 487–499, 2013.